PENGARUH PROFITABILITAS, LIKUIDITAS, DAN INVESTMENT OPPORTUNITY SET (IOS) TERHADAP KUALITAS LABA - Yashinta Markina; Dadang Suhendar; Dendi Purnama (Program Studi Akuntansi, Universitas Kuningan, 2022)
This study aims to determine the effect of Profitability, Liquidity and Investment Opportunity Set (IOS) on Earning Quality. The population obtained is 30 food and beverage companies. The sampling technique used is panel data regression analysis. Based on the result of the simultaneous test, it shows than Profitability, Liquidity and Investment Opportunity Set (IOS) together have a significant positive effect on Earning Quality. Based on the partial test, it shows that Profitability has no significant positive effect on Earning Quality. Liquidity has a significant positive has a significant positive effect on Earning Quality. Investment Opportunity Set (IOS) has no significant positive effect on Earning Quality .Keywords: Earning Quality, Profitability, Liquidity, and Investment Opportunity Set (IOS).